Determinan Fiscal Stress Pemerintah Kabupaten/Kota Provinsi Sumatera Selatan Tahun 2018-2022 - Muhammad Paundra Faza Afdi; Periansya; Sarikadarwati (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
The study aims to determine the impact of PAD growth, capital expenditure growth and economic growth on district/city governance in South Sumatra in 2018-2022. This research is expressive quantitative research using the SPSS 26 adaptation program. The sampling technique used is a classic assumption test by conducting testing to 17 district/city governments in South Sumatera. Additional information from the financial reports of the local government can be accessed at bpk.go.id. In the meantime, the development of capital consumption has no effect on fiscal stress. The Balanced R Square value obtained is about 0.524 which means the great influence of PAD development, capital expenditure growth and financial growth on Fiscal Stress in districts/cities in Sumsel Province is about 52%, which indicates if there is a relationship between autonomous factors and subordinate variables. By studying the variables that affect fiscal stress, this can help local governments to understand and monitor the potential financial risks, to improve the financial health and resilience of the local government to provide services open to the public.